DISCRIMINACION DE INDIVIDUOS COLOMBIANOS CON SINDROME DE DOWN MEDIANTE DERMATOGLIFOS - Vargas Quintero, María Victoria; Departamento de Biología, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá (2013)
A sample of 51 colombian carriers of free G 1 trisomy and 93 controls were studied by taking their handprints. We used both W ALKER (1957) and BOOLLING (1970) methods, which take up to 50 variables into account, to discriminate control population from affected individuals. 41% of individuals with G 1 trisomy was correctly classified through the first method, while 93% were so classified through the second one. We then used multiple stepwise regression to select only 13 variables, which were the utilized in the Boolling method obtaining 92% correct classification.